Mediasi Daya Inovasi dalam Hubungan antara Perencanaan Strategis dan Pembelajaran Organisasi terhadap Kinerja Organisasi - Hernawan, Ito Septanto; Lukiastuti, Fitri (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
power on organizational performance. Strategic planning, organizational learning on innovative power. Mediation of innovative power on the influence of planning strategy and organizational learning on organizational performance. The population in this study were all company managers, totaling 45 people, all of whom were used as samples. Data analysis in this study used Partial Least Squares Structural Equation Modeling (PLS-SEM). The research results show that planning strategy, organizational learning and innovative power have a positive and significant effect on organizational performance, planning strategy, organizational learning have a positive and significant effect on innovative power. Innovation power is able to mediate the relationship between strategic planning and organizational learning on organizational performance with complementary characteristics